Enhancing profitability of nomadic Gaddi goat production system for augmenting farmer’s income - NARENDER KUMAR, P.K. DOGRA1, VARUN SANKHYAN ANJALI KUMARI, ANKAJ THAKUR (Indian Journal of Animal Production and Management, 2020)
Gaddi is a distinct tribe of nomadic pastoralists of Himachal Pradesh involved in rearing of sheep and goats of Gaddi breed. Their flocks are managed totally under extensive (migratory) production system. During summers the flocks climb to high altitude alpine Himalayan pastures and during winters they are grazed in the foot hills. The present study was conducted on Gaddi goats maintained by the Gaddi shepherds under AICRP on Goat Improvement (2010-17). The animals were provided strategic breeding, feeding and health inputs under field conditions and periodic data recordings were done. The overall net income from the sale of surplus and culled animals ranged between Rs. 5.2 to 13.04 lac per annum. The net income per animal per year was observed in the range of Rs. 743.93 and 1120.74. The percent change in overall net income and net income per animal per year recorded during the period (2010-17) was to the tune of 129.42 and 43.24 percent, respectively. This study has demonstrated that nomadic goat farming can be made a profitable and economically viable enterprise by providing critical inputs to overcome the existing constraints